(untitled) (Tanzania Medical Journal, 2015)
This is a review of pulmonary tuberculosis in pregnancy with special emphasis on co-infection with HIV and the situation in Sub Saharan Africa. PTB in conjunction with HIV has significantly impacted maternal morbidity, mortality and poor pregnancy outcomes in Sub Saharan Africa. Active tuberculosis is often asymptomatic or initially masked by the physiologic changes of pregnancy. Further more, most active PTB cases in pregnancy are smear negative for Acid Fast Bacilli. The diagnostic complexity reaches a maximum in HIV positive pregnant women. These findings necessitate more serious thought on the issue of targeted TB screening during pregnancy keeping in mind the consequences of late diagnosis and the specific needs and vulnerabilities of both mother and fetus.